Protein recovery for tissue repair - Saartok, T. (2001)
The neuromuscular system and skeletal muscle are the locomotion systems, or 'engines' of movement in tennis. After work, these muscles need refilling with fuel and fluid, such as carbohydrates and water. However, muscular work also results in 'tearing' of the supporting and working tissue, consisting primarily of protein. During work or exercise, there is always a net catabolism, or 'breakdown' of muscle protein, since protein degradation always exceeds protein synthesis during work. The recovery period (the rest period between a training session or match and the start of the next exercise session) is important, as this is when muscle tissue repairs itself by net anabolism (building and repair of muscle protein). The basic mechanism for this is the 'training-transcription coupling', which refers to the fact that training and exercise affect tissue metabolism directly, through DNA. Hormones, cytokines and other regulatory factors also affect this mechanism. A similar mechanism of up and down-regulation of small proteins, such as enzymes, seems to operate in both tissue repair and performance enhancement (the training effect). Recent research suggests that protein resynthesis and recovery is most efficient in the period immediately after exercise. After strength training, the net synthesis is about four times more efficient in the first four hours after exercise than during 12 to 16 hours after exercise. A combination of carbohydrates and protein seems to be most effective for such recovery, since if energy is not restored, protein will be broken down to provide an energy source. Consequently, intake of protein and carbohydrates soon after a tennis game or practice session is advisable for optimum recovery and repair of muscle tissue. The role of other nutrients, such as fats and anti-oxidants, in this recovery process is currently under investigation. In summary, the timing and content of nutrition after exercise play a key role in the effective repair of supporting and working protein tissue in skeletal muscle. Sufficient sleep and psychological well being are other important contributory factors in the recovery process, due partly to the hormonal systems involved. An insufficient recovery period may lead to both overtraining symptoms and injury. The recovery and repair process for other protein-rich tissues such as tendons and ligaments is probably very similar, but since this occurs at a much lower metabolic rate, these tissues are more difficult to study. The recovery of nervous tissue is still poorly understood. Optimal protein (and carbohydrate) recovery may diminish the risk of both acute and overuse injuries, as well as the risk of overtraining symptoms.